FG syndrome in a Brazilian child with additional previously unreported signs. - Richieri-Costa, A. (Wiley, 1986)
We report on a Brazilian child with typical manifestations of the FG syndrome. Pigmentary dysplasia, metacarpal fusion and peculiar anatomopathological findings are additional undescribed signs.
Keywords: Brazil; case report; dermatoglyphics; human; male; multiple malformation syndrome; preschool child; radiography; syndrome; Abnormalities, Multiple; Case Report; Child, Preschool; Dermatoglyphics; Human; Male; Support, Non-U.S. Gov't; Syndrome